Role of microbiota in pain: From bench to bedside - Huiguang Ren; Bo Cao; Qixuan Xu; Ruiyang Zhao; Hanghang Li; Bo Wei (iMetaOmics)
Abstract Interactions between the microbiota and host have been proven to be critical regulators of homeostasis, and pain perception is no exception. Emerging evidence has identified the mechanisms by which microbiota dysbiosis contributes to hyperalgesia and revealed the potential value of microbiota‐associated therapies in pain management. Herein, the authors introduce the basic knowledge of pain and microbiota for readers who are not simultaneously majoring in these two fields. The clarified mechanisms underlying the regulation of pain by the microbiota are outlined in terms of three ways. This review summarizes the current advancements in pain management and microbiology research for clinicians who wish to focus on this area. Probiotics, fecal microbiota transplantation, and other methods of microbiota modulation for pain management have entered clinical translation. The authors further propose the present limitations and prospects for high‐quality development of preclinical and clinical investigations. Importantly, despite the large amount of attention given to gut bacteria, this review also puts forward great expectations on the role of nongut and nonbacterial microbiota in pain sensation. Efforts to decipher the mechanisms of microbiota functions will help to promote achievements in pain management from bench to bedside.